Structural behaviour of composite dowels in thin UHPC elements. Issue 2 (May 2016) - Lechner, Thomas; Gehrlein, Sebastian Felix; Fischer, Oliver
Abstract: Composite dowels with different shapes have been developed and used in composite members during the last two decades. At the Chair of Concrete and Masonry Structures at Technical University of Munich (TUM), composite dowels with a clothoid shape are used for filigree composite beams and columns. In both types of application the composite dowels are used as external reinforcement and Ultra‐High Performance Concrete (UHPC) is chosen instead of normal‐strength concrete. This article describes mainly the results of the preliminary push‐out tests that were carried out in order to determine the structural behaviour of composite dowels in thin UHPC elements and verify the influence of the UHPC web thickness, the steel thickness of the shear connector, the concrete compressive strength and the influence of reinforcement on the loadbearing capacity and failure modes. The paper also includes an overview of and the outlook for the experiments with composite beams and composite columns.